Monitoring and evaluation for capacity strengthening - Babu, Suresh Chandra (International Food Policy Research Institute, 2018)
Capacity challenges thwart economic growth and development. Efforts to strengthen capacity can benefit from past lessons and documented best practices. This note uses IFPRI’s capacity-strengthening activities as an example to provide an overview of best practices for one of the key elements of capacity development: monitoring and evaluation (M&E). The United Nations Development Programme (UNDP) defines capacity strengthening as the “process through which individuals, organizations, and societies obtain, strengthen, and maintain capabilities to set and achieve their own development objectives over time.”1 Using the UNDP definition, this note explains the concepts of monitoring and evaluation and outlines how to conduct M&E of capacity-strengthening activities, including how to assess inputs, outputs, outcomes, and impact at the individual, institutional, and system levels.